Phylogenetic origin of an insect fauna at the boundary of the Palaearctic and Oriental realms: Evidence from ‘site‐based’ mitogenomics - Rui‐E Nie; Lu‐Lu Li; Anderson Feijó; Mei‐Xia Yang; Ming Bai; Thomas J. Creedy; Xu Jin; Jia‐Sheng Hao; Yong‐Ying Ruan; Hua‐Xi Liu; Beulah H. Garner; Ladislav Bocak; et al. (Journal of Biogeography, 2024)
Aim Knowledge of taxonomy and species distributions in highly diverse lineages of invertebrates remains too incomplete for the study of biogeographical patterns at the global scale. This limits the understanding of processes leading to the formation and maintenance of boundaries between major biogeographical realms. Site‐based metagenomic approaches may provide an alternative source of data for inference of historical processes of in situ speciation and interchange among biogeographical regions. We applied the methodology to explore the historical biogeography of the Qinling Mountains at the boundary of the Oriental and Palaearctic regions. Location The focal area in the Qinling Mountains; sites in Borneo, Panama, and Spain, representing the Oriental, Neotropical and Palaearctic faunas. Time Period Contemporary. Major Taxa Studied Chrysomelidae, a group of ~40,000 species with worldwide distribution. Methods Mass‐trapped insects were subjected to deep Illumina DNA sequencing and mitochondrial genome assembly, followed by phylogenetic analysis and historical biogeographical inference on a dated tree. The methodology produced 622 mitogenomes (304 newly sequenced) each representing a morphologically distinct species. Results Ancestral area reconstruction revealed that the Qinling fauna is a composite of distinct clades that, respectively, have Oriental or Palaearctic ancient origins, while in situ speciation and local clade formation were limited. The global diversity of Chrysomelidae consists of regionalised deep clades at the level of the major zoogeographic realms, which remain recognisable where these realms abut in the Qinling mountains. Yet, the Qinling fauna is clearly distinct from the source areas although local lineage ages are generally Main Conclusions The Qinling fauna is a composite of clades that have either Oriental or Palaearctic origin, indicating the important role of immigration at the realm boundary. Global site‐based phylogenetic analyses based on metagenomic sequencing can address previously intractable questions about the historical biogeography of poorly studied groups even without a fully developed taxonomy.